Swedish Church Customs 1962 - Lund University Church History Archive, Lund University (Lund University, 2013)
Lund University Church History Archive was founded in 1942. The task was to explain and document how the life and manners of the Swedish people was rooted in Christian belief and church customs. Parallel with the investigations of the older church customs the Church Archive started to examine the changes of the contemporary church customs. To get a view of the usage of different customs in the country at the same point of time, a questionnaire was sent to all parishes in 1962. The questionnaire included questions on customs in connection with the general services and at church festivals, and also at different church ceremonies such as christenings, confirmations, marriages and funerals. This nationwide inventory has been repeated in 1968, 1974, 1980, 1986, 1995, 2002 and in 2008/2009.

Purpose:

To identify changes in the contemporary church practice.

Kyrkohistoriska arkivet vid Lunds universitet (LUKA) startade 1942. Uppgiften var då att genom intervjuer och uppteckningar klarlägga och dokumentera folklivets förankring i kristen tro och kyrklig sed.
Parallellt med inventeringarna av den äldre kyrkliga seden började Kyrkohistoriska arkivet på 1940-talet arbeta med att klarlägga förändringar i den samtida kyrkliga seden. Insamlingen av material för att belysa dessa frågeställningar fann sin form under 1960-talet då Kyrkohistoriska arkivet började sända ut rikstäckande frågelistor om den aktuella kyrkliga seden och därmed få en bild av olika företeelsers förekomst i hela landet vid ett och samma tillfälle. Genom sådana 'LUKA-listor' har den kyrkliga seden på olika områden inventerats för hela landet åren 1962, 1968, 1974, 1980, 1986, 1995, 2002 samt 2008/2009.

De första sju undersökningarna inom Svensk kyrklig sed är utförda på församlingsnivå. I den senaste undersökningen, från 2008-2009, är frågorna istället besvarade på pastoratsnivå. Det innebär att vissa till synes motsägelsefulla uppgifter förekommer. Detta är dock resultatet av att frågorna besvarats utifrån förhållanden i skilda församlingar inom samma pastorat, där seden skilt sig åt.

Syfte:

Att kartlägga förändringar i den samtida kyrkliga seden.
Svensk kyrklig sed 1962
Keywords: religion; religion; religious attendance; religiöst deltagande; church; kyrka; customs and traditions; seder och bruk; baptisms; dop; weddings; bröllop; ministers of religion; präster; Cultural activities and participation; Kulturaktiviteter och deltagande; Religion and values; Religion och värderingar; Religious Studies; Religionsvetenskap; History of Religions; Religionshistoria